ANALYSIS OF THE PROFITABILITY OF RETRO AIR JORDAN SNEAKERS AS AN ALTERNATIVE INVESTMENT STRATEGY - BUDIMAN, PRADIPTO BHASKORO SUSILO (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study examined Retro Air Jordan sneakers as a collectible good; analyzing its profitability as an alternative investment compared to stocks for the period of 2016. Utilizing a quantitative descriptive approach, the returns of 20 sample Retro Air Jordans were assessed using the buy and hold strategy. In addition, the returns were then compared against the performance of the top 21 companies listed in the S&P 500 using both the buy and hold strategy and the 20-day simple moving average. The results provided no evidence that the sample Retro Air Jordans, on average, were able to outperform the sample S&P 500 stocks. However, the study revealed that the sample Retro Air Jordans were able to generate significantly higher returns against the sample S&P 500 stocks (3.37 times higher to be exact) when bought at their individual retail price and held over the same study period. These results seem to suggest that collectibles, specifically Retro Air Jordans, are profitable as an alternative investment if collected and sold for resale value.Keywords: collectibles, alternative investment, buy and hold, simple moving average, retro air jordan, sneakers, trading strategy